THE EFFECT OF LAND AND BUILDING TAX AND LAND BUILDING REGHTS ACQUISITION DUTY ON LOCAL OWN – SOURCE REVENUE IN BEKASI REGENCY 2020-2024 - Herlina Puspa Dewi; Shakilla Shahwa Hafiza (Jurnal Investasi, 2026)
This study examines the influence of Land and Building Tax and Land and Building Rights Acquisition Duty on Local Own-Source Revenue in Bekasi Regency from 2020 to 2024. The objective is to determine the extent to which these taxes contribute to strengthening regional revenue. The research applies a quantitative approach using multiple linear regression based on secondary data obtained from regional revenue reports. The findings show that both taxes have a positive and significant effect, with Land and Building Rights Acquisition Duty demonstrating a stronger impact. The study recommends improving tax data accuracy and enhancing digital administration to optimize revenue performance. Keywords: Pajak Bumi dan Bangunan, Bea Perolehan Hak atas Tanah dan Bangunan, Pendapatan Asli Daerah.